Decentralized models of agricultural marketing as a strategy for social inclusion in Colombia: the case Exofruit SAS - Arias Vargas, Francisco (2015)
This paper analyzes a model of decentralized marketing cape gooseberry (Physalis peruviana) as an alternative to traditional wholesale channels; where brokers obtain higher profits; while farmers receive little profit for their product and the customer receives an expensive product. The investigative process development for nine months under a descriptive exploratory approach to data collection and triangulation of it to build the case. The project currently benefits 40 farmers; victims of armed conflict in the village of Mesopotamia Antioquia Union have joined the project, which has particularities like organic production of 1.2 tons per month of product, recovery of abandoned land; and equitable distribution of profits and the way for negotiations between farmers and the seller as a new proposal of peasant association.